The Issue of Human Dignity and Rights from The Viewpoint of Abu Nasr Forabi - Musayev Fahriddin Abdusattorovich (Scientific Trends, 2025)
This article analyzes the philosophical and moral views of Abu Nasr Forabi, a great thinker of the Eastern Renaissance, on human dignity and human rights. In Al-Farabi's work "The City of Virtuous People", the essence of the relationship between man, society and the state, the importance of the principles of the rule of law and justice are revealed. The author's teachings are analyzed from the point of view of their compatibility with the principles of a modern democratic society.
Keywords: Abu Nasr Forabi, human dignity, human rights, virtuous society, rule of law, justice, spiritual perfection.